Representations of Loneliness in Peter Parker's Character in "The Amazing Spider-Man" Films - Marshanda, Aurellia; Setyabudi, Titis (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
This study aims to deeply analyze the form, portrayal, and psychological motives of Peter Parker's loneliness in the films The Amazing Spider-Man (2012) and The Amazing Spider-Man 2 (2014). This research uses an interpretive qualitative approach with a narrative and visual content analysis design. Primary data is taken from scenes, dialog, and cinematic elements. The analysis phase was conducted systematically: (1) Classification of loneliness aspects based on Weiss/Cacioppo Theory, (2) Identification of supporting cinematic elements (e.g., mise-en-scène), and (3) Triangulation with Alfred Adler's Individual Psychology concepts (Inferiority Complex, Striving for Superiority, and Lifestyle) to determine the root causes of loneliness. It was found that Peter Parker's loneliness is multidimensional, encompassing Emotional Loneliness (Feelings of Loss and Intimate Relationship Difficulties) and Social Loneliness (Social Isolation). Visually, the isolation is reinforced thru low-key lighting and rain symbols, emphasizing its emotional weight. Causally, loneliness is a consequence of a Solitary Lifestyle formed as compensation for feelings of inferiority resulting from childhood trauma and conflict between Social Interest (hero's responsibility) and personal needs. The novelty of this study lies in the explicit integration of Adler's Individual Psychology Theory and Loneliness Theory to analyze fictional superhero characters. This research provides a deep psychological analysis model not previously available in previous studies, explaining that Peter's loneliness is a structural price of heroic responsibility, not merely interpersonal failure.